Kemampuan Computational Thinking Siswa Ditinjau dari Adversity Quotient dan Gender di MTs Negeri Lombok Tengah - Firza, M. Sandi; Negara, Habibi Ratu Perwira; Mahfudy, Sofyan (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
This study aims to explain the computational thinking ability of students at MTs Negeri 2 in Central Lombok in terms of adversity quotient and gender. The research method used is a quantitative approach with a causal-comparative research design. The research sample consisted of 136 grade VIII students, consisting of 62 male students and 74 female students. The instruments used in this study included a computational thinking ability test consisting of 2 essay questions and a questionnaire to measure adversity quotient with 24 statements. The results of the study showed that: 1) there is a significant effect of adversity quotient on students' computational thinking ability; 2) there is no significant effect of gender on students' computational thinking ability; and 3) the interaction between adversity quotient and gender does not show a significant effect on students' computational thinking ability. The contribution of this study provides new insights into how adversity quotient affects students' computational thinking, which can be the basis for developing more effective learning strategies in the future.